Strongyloides stercoralis hyperinfection associated with impaired intestinal motility disorder - Cláudia Frangioia Figueira; Márcio Teodoro da Costa Gaspar; Lynda Dorene Cos; Edson Yassushi Ussami; José Pinhata Otoch; Aloísio Felipe-Silva (University of São Paulo, 2015)
Infection by Strongyloides stercoralis is a highly prevalent helminthiasis, which is mostly distributed in the tropical and subtropical regions of the world. Although a substantial number of cases are asymptomatic or paucisymtomatic, severe and life-threatening forms of this infection still occur and not infrequently is lately diagnosed. Gram-negative bacteria septicemia, which frequently accompanies the severe helminthiasis, contributes to the high mortality rate. Severe infection is invariably triggered by any imbalance in the host's immunity, favoring the auto-infective cycle, which increases the intraluminal parasite burden enormously. Clinical presentation of severe cases is varied, and diagnosis requires a high suspicion index. Acute abdomen has been reported in association with S. stercoralis infection, but intestinal necrosis is rarely found during the surgical approach. The authors report the case of a man who sought the emergency unit with recent onset abdominal pain. Clinical and imaging features were consistent with obstructive acute abdomen. Scattered adhesions and a necrotic ileal segment with a tiny perforation represented the surgical findings. The patient outcome was unfavorable and respiratory distress required an open lung biopsy. Both surgical specimens showed S. stercoralis infection. Unfortunately the patient underwent multiple organ failure and septicemia, and subsequently died. The authors call attention to the finding of intestinal necrosis and impaired intestinal motility disorder as possibilities for the diagnosis and risk factor, respectively, for a severe infection of S. stercoralis.